PERBANDINGAN KADAR TOTAL KARBON DAN NITROGEN PADA KOMPOS DARI BERBAGAI MACAM JENIS GULMA - Okty Patrechia; Bambang Gonggo Murcitro; Zainal Muktamar; Hasanudin; Muhammad Faiz Barchia (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[COMPARISON OF NUTRIENT CONTENT IN COMPOST DERIVED FROM VARIOUS TYPES OF WEEDS]. Weeds can reduce crop productivity and cause environmental problems. However, thiese plants are potential as sources of compost. This study aimed to compare carbon and nitrogen content of compost prepared from various types of weeds. The research was conducted from February to March 2024 at the Composting House of Bengkulu University in Muara Bangkahulu District, Bengkulu Province. The experiment used a Completely Randomized Design (CRD) with 6 types of weeds, namely, Imperata cylindrica, Eichhornia crassipes, Widelia trilobata, Ageratum conyzoides, Tithonia diversifolia, and Melastoma malabathricum. The experiment was repeated 3 times, so that the total number of experimental units in this study was 18 experimental units. Three kg of compost source was mixed with 100 mL EM4, 200 g of sugar, and 100 mL of water. The mixture was poured into the plastic bowl and incubated for 45 days. Data were analyzed using Analysis of Variance at a level of 5%, and treatment means were separated using Duncan's Multiple Range Test (DMRT) at the 5% level. The study found that compost from all types of weeds had a C/N ratio that met the quality standards for organic fertilizers, ranging from 7.52 to 24.54. Compost made from Tithonia (Tithonia diversifolia) had the highest total nitrogen content (2.58%) and the lowest organic carbon content (19.32%). These findings are significant for the development of sustainable agriculture, mainly the use of weed compost as source of N for plant growth.